2022
DOI: 10.1002/smll.202203918
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Processing of Interfacially Grown Iron‐Oxide Flowers into 2D‐Platelets Yields Lithium‐Ion Battery Anodes with Capacities of Twice the Theoretical Value

Abstract: papers have shown that converting bulk powder to 2D nanosheets yields significant capacity increases. [18][19][20] In addition, 2D platelet-shaped nanoparticles show great potential for use in battery electrodes due to shorter solid state diffusion lengths which can yield improved rate performance. [21] However, high aspect ratio 2D nanosheets can reduce the diffusion coefficient associated with ion transport within the electrolyte filled pores. [21] To avoid slow liquid phase diffusion while maintaining short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 80 publications
2
22
0
Order By: Relevance
“…Abundant pore distributions and relatively disordered structure of carbon have positive effects on the Li‐ion diffusion in the electrode. [ 19 ] Such enhancement is benefit for the rate performance. Under current densities of 0.1C, 0.2C, 0.5C, 1C, and 2C (Figure 3d), the HCSP electrode presents the best rate performance, SCSP the second, and GrSP the third.…”
Section: Resultsmentioning
confidence: 99%
“…Abundant pore distributions and relatively disordered structure of carbon have positive effects on the Li‐ion diffusion in the electrode. [ 19 ] Such enhancement is benefit for the rate performance. Under current densities of 0.1C, 0.2C, 0.5C, 1C, and 2C (Figure 3d), the HCSP electrode presents the best rate performance, SCSP the second, and GrSP the third.…”
Section: Resultsmentioning
confidence: 99%
“…S3a,† the reduction peak at 0.56 V and the oxidation peak at 1.65 V are visible in the initial cycle, which suggested that lithium ions were inserted into the Fe 2 O 3 to generate the solid electrolyte interface (SEI) layer (eqn (4)) 24 and invertible conversion of Fe and Fe 2 O 3 to each other (eqn (1)–(3)). 25,26 Fe 2 O 3 + x Li + + x e − ↔ Li x Fe 2 O 3 Li x Fe 2 O 3 + (2 − x )Li + + (2 − x )e − ↔ Li 2 Fe 2 O 3 Li 2 Fe 2 O 3 + 4Li + + 4e − ↔ 2Fe 0 + 3Li 2 OLi + + e − + electrolyte → SEI (Li)…”
Section: Resultsmentioning
confidence: 99%
“…S3a, † the reduction peak at 0.56 V and the oxidation peak at 1.65 V are visible in the initial cycle, which suggested that lithium ions were inserted into the Fe 2 O 3 to generate the solid electrolyte interface (SEI) layer (eqn (4)) 24 and invertible conversion of Fe and Fe 2 O 3 to each other (eqn (1)-( 3)). 25,26 Fe…”
Section: Preparation and Characterizationmentioning
confidence: 99%
“…Conversion-type Fe 2 O 3 -based electrodes have received extensive attention due to their high theoretical capacity (1007 mAh g –1 ), environmental friendliness, and wide source of raw materials. However, Fe 2 O 3 , similar to other conversion anodes, has poor electrical conductivity (less than 10 –38 S cm –1 at 300 K), resulting in disappointing rate properties, and suffers from large volume changes (∼75%) during battery operation, making it difficult to maintain long life . Strategies such as heteroatomic doping, introducing conductive carbon, , and constructing nanostructures are widely employed to address these issues. Reducing the particle size to the nanometer scale can effectively shorten the Li + ion diffusion path, buffer the volume change, ease the release stress, and thus promote the electrochemical properties .…”
Section: Introductionmentioning
confidence: 99%